1992
DOI: 10.1084/jem.175.2.577
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of the T cell-specific accessory molecules CD7 and CD28 modulates T cell adhesion.

Abstract: SummaryRegulated adhesion enables T cells to migrate through tissue and transiently interact with an endless succession of cells. Monoclonal antibody (mAb) engagement of the CD3/T cell receptor (TCR) complex results in a rapid and transient augmentation of the adhesion function of LFA-1 and VLA integrin molecules on human T cells. We show in this study that mAb crosslinking of the T cell-specific accessory molecules CD7 and CD28, or treatment with the Ca 2+ ionophore A23187, results in the rapid induction of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 32 publications
5
94
0
Order By: Relevance
“…These findings would seem to indicate a co-regulation of ␤ 1 and ␤ 2 integrins through serine-threonine phosphatases. Further evidence for coregulation comes from studies on T cells where activation by cross-linking of CD3, CD7, or CD28 was shown to activate both VLA-4 and LFA-1 [13]. Moreover, CD3 stimulation induces colocalization of both VLA-4 and LFA-1 to F-actin [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings would seem to indicate a co-regulation of ␤ 1 and ␤ 2 integrins through serine-threonine phosphatases. Further evidence for coregulation comes from studies on T cells where activation by cross-linking of CD3, CD7, or CD28 was shown to activate both VLA-4 and LFA-1 [13]. Moreover, CD3 stimulation induces colocalization of both VLA-4 and LFA-1 to F-actin [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the amount of expression of cell surface adhesion molecules, the functional state of integrins can be regulated, leading to changes in the affinity for counterligand binding without affecting the level of cell surface expression [11]. Changes in T cell integrin activity can be induced in vitro by a variety of stimulating agents, such as phorbol esters, calcium ionophore, and cross-linking of T cell receptors like CD2, CD3, CD7, and CD28 [3,[12][13][14]. Furthermore, the activation state of integrins can be altered by antibodies against ␤ 1 integrins, like 8A2, that bind to the receptor and induce a more active form [15] or by alterations of the extracellular cation milieu, both of which appear to affect the conformation of the integrin binding site [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cell-surface receptors, called integrin regulators, can induce an inside-out signal. These integrin regulators include the TCR complex, CD2, CD28, CD7 (Chan et al 1991, Shimizu et al 1992) and cell surface signaling proteins of the transmembrane-4 superfamily that include CD9, CD53, CD63, CD82 and CD81 (Mannion et al 1996).…”
Section: Signaling Via β β β β β1 Integrins On Eosinophilsmentioning
confidence: 99%
“…Ligation of the T cell receptor (TCR), CD2, CD7, and CD28 receptors have all been shown to up-regulate integrin adhesion in a wortmannin-sensitive manner, indicating a requirement for PI 3-K [4][5][6]9]. With regard to outside-in signaling, it has been shown that HPB-ALL T leukemia cells adhere to immobilized fibronectin (FN) through the integrin ␣ 4 ␤ 1 and that this interaction activates phospholipase A 2 (PLA 2 ) to produce arachidonic acid (AA) followed by the formation of cellular pseudopodia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte integrins are normally maintained in a low-affinity conformation and require an up-regulatory signal to form a strong interaction with their specific substrates. Phosphoinositide 3-kinase (PI 3-K) and protein kinase C (PKC) [2][3][4][5][6][7][8] have been implicated as mediators of this cascade, referred to as inside-out signaling [1]. Once activated, the ligand-bound integrin receptor then initiates the production of intracellular signals in the form of classic biochemical messengers and nonclassic mechanical signals.…”
Section: Introductionmentioning
confidence: 99%